Zest-O fresh pick: Integrated marketing campaign - Parca, Angelique Ria A. (Animo Repository, 2020)
Zest-O Corporation first started in 1981, and has been a leading food and beverage Filipino company competing with multinational companies for over 30 years. They have mastered the “doypack” packaging specifically for their RTD juice drinks. In 2017, Zest-O had the fair share of getting hit by the TRAIN Law and the tax it has implied on sugar-sweetened beverages. Thus, Zest-O came up with Fresh Pick. Fresh Pick is a fairly new RTD juice in the market. It was commercially introduced last July 2019 with the unique selling proposition of, “it has no added sugar, its sweetness comes from the natural juices of Orange and Apple and Stevia.” This campaign will further focus on the existing primary target market of Fresh Pick, which are the market B - upper C, millennial parents and their children (preschool to elementary) as the secondary target market. The campaign will mainly utilize the “new media” as the main marketing channel since according to Pew Research, “more than nine-in-ten Millennials own smartphones,” which are about 25% are already parents as of 2017 and it is continually growing. At a rate of more than a million millennials are becoming mothers every year all over the world, which is definitely the biggest contributors to the digital and Fast-moving Consumer Goods (FMCG) markets. With that being said, the brand gave the campaign a 40 million budget, but since the campaign will concentrate on Metro Manila, a portion of the budget will only be utilized, which totaled at Php 8,829,090. The campaign is expected to deliver a general objective of brand awareness for Fresh Pick as the “first choice of parent millennials and go-to healthy pambaon of kids”. This main objective will be part of the goal of every platform that will be utilized in the campaign. This includes the online tools: Facebook, Instagram, Key Online Influencers & Youtube, for the out- of-home platforms; Billboards, School Buses, 7 Eleven stores and lastly for the events marketing part, the Family Day Fun Run event as the finale.